COLLECTIVE MEMORY OF THE WAR IN RUSSIAN AND GERMAN PUBLIC CONSCIOUSNESS - G. N. Rykun (Гуманитарные и юридические исследования)
The article presents two views, two approaches to the memory of the Second World War and the people who blockedfascist movement on the way to world domination. On the one hand, the winners which keep sacred memory of the soldiers who defended the country from enslavement, on the other hand, the losers who honor the deserters, who left the battlefield or refused to serve in the Wehrmacht. The author believes that modern German society has to do itto get rid of the guilt of the war unleashed by Nazis. At the same time, according to the author, this approach does not unite, but rather divides German society, divides it into supporters and opponents of this kind of memory. The memory of the War, in his opinion, should be based only on truth, on a sincere respect for the people who gave their lives for their country, which excludes any attempt of falsification and substitution of real events of wartime.